(3GdGZJHGW HTQM fRgI GdGfHSGWs - (3CHhRjO YHO GdQMef Hf YHO GdbGOQ GdaGSjs; (3GdeQLGfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi SdN ef bHd GdLgGdI fgGQ GdeYQaI s
(3BNQgG (B:s
(3dGJfbWY GdOYhI hgh MSHfG hfYe Ghcjd hUdi Gddg Yi SjOfG eMeO NGJe GdfHjjf hEeGe GdeQSdjf hGNQ OYhGfG Gf GdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs